2016
DOI: 10.1016/j.jsat.2016.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Linkage to Primary Care for Persons First Receiving Injectable Naltrexone During Inpatient Opioid Detoxification

Abstract: Introduction Opioid use disorders commonly require ongoing medication-assisted treatment to reduce relapse following discharge from inpatient detoxification programs. Naltrexone, an opioid antagonist, is an increasingly popular treatment option in its once-monthly injectable form (XR-NTX). The aim of this study was to examine the follow-up rates of persons who received an initial injection during inpatient detoxification and scheduled for receipt of a first outpatient injection in the primary care setting. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Eight studies (44, 45, 48, 50, 55, 60, 61, 64) reported whether a variety of participant factors (e.g., demographics, drug use) were associated with XR-NTX adherence (Supplemental Table 2). Some variables were related to adherence but many of the associations were inconsistent across studies or reported only by one study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight studies (44, 45, 48, 50, 55, 60, 61, 64) reported whether a variety of participant factors (e.g., demographics, drug use) were associated with XR-NTX adherence (Supplemental Table 2). Some variables were related to adherence but many of the associations were inconsistent across studies or reported only by one study.…”
Section: Resultsmentioning
confidence: 99%
“…Seven retrospective studies reported adherence outcomes [22,53,54,[59][60][61][62] (Table 4). Observation periods were generally approximately 6 months long.…”
Section: Retrospective Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Strategies such as extended‐release medication formulations may help to overcome some of the adherence challenges presented by daily medications. However, even with this advantage, many barriers to retention remain [20,21]. Several studies have examined the impact of extended‐release naltrexone (XR‐NTX) on youth treatment.…”
Section: Introductionmentioning
confidence: 99%
“…An extended-release injectable suspension of naltrexone (XR-NTX) was developed and is approved for the treatment of opioid use disorder in the United States. XR-NTX appears to improve adherence compared to oral naltrexone [4], but adherence rates are still poor [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%